The Timeliness of the Bond Market Reaction to Bad Earnings News - Defond, Mark L.; Zhang, Jieying (Contemporary Accounting Research, 2014)
We find that bond price quotes impound bad earnings news on a more timely basis than good earnings news and that the bond market impounds bad news on a more timely basis than the stock market. We also find that the timeliness of the bond market reaction to bad news is concentrated primarily among speculative‐grade bonds, consistent with earnings news having a larger effect on bond price quotes when default risk is high. In addition, we find that a portion of the bad news impounded by the bond market reverses following the earnings announcement. Overall, our findings are consistent with bondholders’ asymmetric payoff function having important implications for the valuation role of accounting information in the bond market. Specifically, our findings indicate that bond quotes impound bad earnings news much earlier in the pre‐earnings announcement period than stock prices. In addition, bondholders appear to overreact to the bad earnings news initially and correct this overreaction subsequent to the earnings announcement.